On the chronology of the Anonymous Commentary to Ptolemy’s Tetrabiblos: Analysis of the astronomical evidence. - Caballero-Sánchez, José Raúl (Sage, 2021)
In this paper, a proposal is made that the Anonymous Commentary to Ptolemy’s Tetrabiblos (Anon. in Ptol.) was composed not before 467 and not after 575 AD. In establishing the terminus post quem and the terminus ante quem, the Author relies on astronomical data provided by the Anonymous himself in his commentary to Ptolemy, Tetrabiblos (=Ptol. Tetr.) II.10 (p. 76, ll. 16-29 Wolf). In this passage, he reports that his master completely succeeded in interpreting the appearance of a celestial beam (δοκός) as a sign of a great loss of trunks, after which a naval battle took place where many ships were sunk; moreover, the master of the anonymous commentator predicted that the comet would remain visible until the end of Mercury’s retrogradation, and so it happened. As will be seen below, it is possible to crosscheck all this data to obtain a precise date of the comet’s appearance: 467 AD, 1 year before the naval battle of Cape Bon (468 AD). These years are also consistent with the dating that can be obtained from one of the horoscopes transmitted by the anonymous commentary (p. 98 Wolf), which corresponds to a birth that actually took place in Lower Egypt on 25 June 448 AD.
https://openpolicyfinder.jisc.ac.uk/id/publication/30008
Keywords: Astrología griega; Ptolomeo, Claudio - Crítica e interpetación; Chronology; Greek astrology; Ptolemy; Tetrabiblos; Anonymous commentary